2018
DOI: 10.1097/njh.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of the Home Health Nursing Shortage on Family Caregivers of Children Receiving Palliative Care

Abstract: The national nursing shortage translates into a gap in home nursing care available to children with complex, chronic medical conditions and their family caregivers receiving palliative care consultations. A total of 38 home health nursing surveys were completed by families receiving pediatric palliative care consultation services at a freestanding children's hospital in the Midwest. The gap in the average number of nursing hours allotted versus received was 40 h/wk per family, primarily during evening hours. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…Similar to Suzuki, Sato, Emoto, & Kamibeppu (2017) support from home health nurses was reported as one of the top most helpful subthemes. However, consistent with prior research, home health nurses were also identified as least helpful due to last minute cancellations of their shift and other staffing issues (Weaver et al, 2018). One mother reported, "The nursing agency is not able to cover scheduled shifts of care for my child".…”
Section: Discussionsupporting
confidence: 54%
“…Similar to Suzuki, Sato, Emoto, & Kamibeppu (2017) support from home health nurses was reported as one of the top most helpful subthemes. However, consistent with prior research, home health nurses were also identified as least helpful due to last minute cancellations of their shift and other staffing issues (Weaver et al, 2018). One mother reported, "The nursing agency is not able to cover scheduled shifts of care for my child".…”
Section: Discussionsupporting
confidence: 54%
“…Tracheostomy discussions warrant consideration of: survival trajectory and prognostic duration, healthcare dependence, whether airway interventions fosters the family's subjective definition of quality of life for the child, the ways a tracheostomy may impact the child's ability to vocalize or take food by mouth, potential benefits or burdens to the child in the context of the child's additional comorbidities, and expected functional status with life prolongation by tracheostomy support (Bice, Nelson, & Carson, 2015; Wallis, Paton, Beaton, & Jardine, 2011). In the context of the national home health nursing shortage, technology advancement may prohibit a child from residing in the family home as compared to a skilled nursing facility (Weaver, Wichman, et al, 2018). Thus, if a family's primary goal is for the child to be physically home rather than an inpatient or skilled nursing setting, realistic discussion about care location feasibility should thoughtfully be partnered with conversations about tracheostomy placement.…”
Section: Otolaryngologymentioning
confidence: 99%
“…When home health resources are lacking, unfilled shifts fall squarely on the shoulders of family caregivers, and impact parent sleep, physical and mental health, and employment status. Unmet nursing needs become the responsibility of family caregivers 10,23,24 who often experience resulting financial and emotional strain 3,11,25–28 …”
Section: Discussionmentioning
confidence: 99%
“…Supreme Court decision 1 . However, private duty and block home nursing services that allow these children to safely live in the community are limited, 2–5 increasing the responsibilities of family caregivers, often to the detriment of their employment and health 6–11 . Further, home nursing shortages are associated with increased length of hospital stay for children with new technologies 12,13 …”
Section: Introductionmentioning
confidence: 99%